Development of a Web-Based Nonoperative Small Bowel Obstruction Treatment Pathway App - Lyu, Heather; Manca, Caitlin; McGrath, Casey; Beloff, Jennifer; Plaks, Nina; Postilnik, Anatoly; Borchers, Amanda; Diaz, Nicasio; McGovern, Sean; Havens, Joaquim; Kachalia, Allen; Landman, Adam (Applied Clinical Informatics, 2020)
Objective An electronic pathway for the management of adhesive small bowel obstruction (SBO) was built and implemented on top of the electronic health record. The aims of this study are to describe the development of the electronic pathway and to report early outcomes.Methods The electronic SBO pathway was designed and implemented at a single institution. All patients admitted to a surgical service with a diagnosis of adhesive SBO were enrolled. Outcomes were compared across three time periods: (1) patients not placed on either pathway from September 2013 through December 2014, (2) patients enrolled in the paper pathway from January 2017 through January 2018, and (3) patients enrolled in the electronic pathway from March through October 2018. The electronic SBO pathway pulls real-time data from the electronic health record to prepopulate the evidence-based algorithm. Outcomes measured included length of stay (LOS), time to surgery, readmission, surgery, and need for bowel resection. Comparative analyses were completed with Pearson's chi-squared, analysis of variance, and Kruskal–Wallis tests.Results There were 46 patients enrolled in the electronic pathway compared with 93 patients on the paper pathway, and 101 nonpathway patients. Median LOS was lower in both pathway cohorts compared with those not on either pathway (3 days [range 1–11] vs. 3 days [range 1–27] vs. 4 days [range 1–13], p = 0.04). Rates of readmission, surgery, time to surgery, and bowel resection were not significantly different across the three groups.Conclusion It is feasible to implement and utilize an electronic, evidence-based clinical pathway for adhesive SBOs. Use of the electronic and paper pathways was associated with decreased hospital LOS for patients with adhesive SBOs.
Keywords: pathways; digital health; Web-based application; EHR; surgery